Life is a wheel : love, death, etc., and a bike ride across America - Weber, Bruce, 1953- (New York : Scribner, 2014)
"Based on his popular series in the New York Times chronicling his cross-country bicycle trip, bestselling author Bruce Weber shares his adventures from his solo ride across the USA. Riding a bicycle across the US is one of those bucket-list goals that many dream about but few achieve. Bestselling author and New York Times reporter Bruce Weber made the trip, solo, over the summer and fall of 2011--at the age of fifty-seven. Expanding upon his popular series published in The New York Times, Life Is a Wheel is the witty and inspiring account of his journey, where he extols the pleasures of cycling and reflects on what happened on his adventure, in the world, in the country, and in his life. The story begins on the Oregon coast with a middle-aged man wondering what he's gotten himself into and ends in triumph on the George Washington Bridge, wondering how soon he might try it again. Part travelogue, part memoir, part paean to the bicycle as a simple and elegant mode of both mobility and self-expression--and part wry and panicky account of a fifty-seven-year-old man's attempt to stave off mortality--Life Is a Wheel is an elegant and entertaining escape for any armchair traveler"--
Keywords: Weber, Bruce, -- 1953- -- Travel. -- United States; Cycling -- United States; Cycling -- Psychological aspects; Middle aged men -- United States -- Biography; Self-reliance -- United States; Mortality -- Social aspects -- United States; BIOGRAPHY & AUTOBIOGRAPHY / Personal Memoirs; TRAVEL / United States / General; SPORTS & RECREATION / Cycling; United States -- Description and travel; United States -- Social life and customs -- 1971-